Spectroscopic parameters of advanced detectors based on gallium germanium garnet Ce : GAGG - Kozlov, Dzmitry Yu.; Korjik, Mikhail V.; Lobko, Alexandr S.; Fedorov, Andrey A.; Mechinsky, Vitaly A.; Bogomolov, Vitaly V.; Iyudin, Anatoly F.; Svertilov, Sergey I.; Yashin, Ivan V. (Journal of the Belarusian State University. Physics, 2019)
The results of measurements of the energy resolution of advanced scintillation crystal Ce : GAGG grown in the Research Institute for Nuclear Problems of the Belarusian State University are considered. The measurements were carried out in the energy range of detected gamma quanta from 20 keV to 3 MeV. A rectangular sample with size of 12 × 12 × 9 mm was studied. Photomultiplier Hamamatsu R3998-100-02, avalanche photodiode S8664-1010 and silicon matrices (SiPM) manufactured by SensL were used as photodetectors. The measured energy resolution on the  137 Cs line (662 keV) was about 7.5 %, which is not inferior to the resolution of the widely used NaI(Tl), CsI(Tl) scintillators of a similar size. Since Ce : GAGG crystals are not hygroscopic and compared to NaI(Tl), CsI(Tl) are characterized by a significantly shorter decay time (~ 80 ns), they seem very promising for use in gamma spectrometers and as position-resolvable elements of spatially sensitive detectors of energetic particles and gamma quanta.
Keywords: scintillator; crystal; detector; isotope; gamma quanta; pulse; energy resolution